Early and late complications after surgical treatment of oesophageal cancer - Bała, Dariusz; Jankowski, Michał; Zegarski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2007)
Background : Oesophageal cancer is a neoplasm with poor prognosis and high risk of complications and mortality after surgery. Aim of study : To evaluate complications after surgical treatment of oesophageal cancer. Material and methods : Between 2000 and 2005 in the Department of Surgical Oncology in Bydgoszcz there were performed 34 radical resections of the oesophagus on patients with oesophageal cancer. Results : Shortly after the operations, complications occurred in 17 patients (50%). In 12 cases these complications were severe (bleeding – 2, anastomotic leak – 5, cardiovascular and respiratory disorders – 3, pneumonia – 3); mortality – 0%. Late complications appeared in 9 patients after some period of time (anastomotic stricture – 9, bile reflux – 2). Up till today, treatment has been unsuccessful in 19 patients (55.8%). Conclusions : Oesophagectomy in patients with oesophageal cancer is still characterized by high (50%) morbidity. The most common cause of mortality is distant metastases.